2016
DOI: 10.1208/s12249-016-0487-1
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Bovine Serum Albumin-Loaded Niosome

Abstract: Abstract. Niosomal vesicle, as a unique novel drug delivery system, is synthesized by non-ionic surfactants. Both hydrophilic and lipophilic drugs and also biomacromolecular agents, such as peptides and proteins can be encapsulated in this vesicular particle. Regarding polypeptide-based component loading, and delivery potential of the niosome, some valuable studies have been conducted in recent years. However, exploring the full potential of this approach requires fine tuned optimization and characterization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 34 publications
8
38
0
1
Order By: Relevance
“…The authors found that both nanoparticles resulted in higher IgG in serum from BSA compared to the controls, but that niosomes were generally more effective than liposomes. A follow‐up study was performed by Omidfar and co‐workers to optimize the release rate of BSA from niosomes . Most recently, Bhatnagar and co‐workers developed niosomes to deliver protective antigens for immunization against an anthrax spore challenge in mice .…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that both nanoparticles resulted in higher IgG in serum from BSA compared to the controls, but that niosomes were generally more effective than liposomes. A follow‐up study was performed by Omidfar and co‐workers to optimize the release rate of BSA from niosomes . Most recently, Bhatnagar and co‐workers developed niosomes to deliver protective antigens for immunization against an anthrax spore challenge in mice .…”
Section: Microscale Materials For Immunotherapymentioning
confidence: 99%
“…A follow-up study was performed by Omidfar and co-workers to optimize the release rate of BSA from niosomes. [363] Most recently, Bhatnagar and co-workers developed niosomes to deliver protective antigens for immunization against an anthrax spore challenge in mice. [364] While there are still relatively few examples of niosomes used in immunotherapy, we believe this is an auspicious vehicle for translation due to its immunogenic performance, scale and ease of formulation, and low cost.…”
Section: Niosomesmentioning
confidence: 99%
“…Firstly, a formulation optimization study was conducted and BSA release properties of niosomes determined. This investigation additionally showed a cost-effective method for BSA quantification in niosomes and similar vesicles (8). Secondly, similar span 60 and cholesterol niosomes were loaded with basic fibroblast growth factor, incorporated in agarose hydrogel as a scaffold, and evaluated for their in vitro cell proliferation performance (9).…”
mentioning
confidence: 92%
“…In an alternative approach for macromolecule drug formulation in nanostructured systems, two articles detail the development and characterization of niosomes as delivery systems (8,9). Firstly, a formulation optimization study was conducted and BSA release properties of niosomes determined.…”
mentioning
confidence: 99%
“…Moghassemi et al [124] formulated bovine serum albumin-loaded niosomes that have potential use in pharmaceutical and cosmetic applications.…”
Section: Other Applicationsmentioning
confidence: 99%